التطبيق المصرفي لعقد الإجارة ثم البيع في ماليزيا: دراسة فقهية نقدية = Banking application of Al-Ijarah Thumma al-Bay’ (AITAB) contract in Malaysia: a juristic and critical study - Mat Jubri@Shamsuddin, Mustafa; Sitiris, Miszairi (The Scientific Institute For Advanced Training and Studies, 2018)
The contract of al-Ijarah Thumma al-Bay’ (AITAB) has been categorized as among financing contracts which applied in Islamic Financial Institutions in Malaysia. This research concentrates on the application’s aspect of AITAB with special attention to the sides where this contract does not comply with the Islamic legal principles and objectives. This research attempts to scrutinize the application process of this contract in Islamic Financial Institutions, and therefore to distinguish the part of it which complies with Shariah and the part which contradict. The biggest obstacle of making this contract fully in line with Shariah is its subjection to the Civil Law. Thus, this research proposes some solutions in order to get rid from this issue of application and come out with appropriate Fiqh Adaptation (Takyif Fiqhi) for this contract.